PENGEMBANGAN KAWASAN INDUSTRI DI INDONESIA - Timoticin Kwanda (DIMENSI (Journal of Architecture and Built Environment), 2000)
In Indonesia, at the first time industrial estates were developed in 1970's by the government through the state owned company as a reaction to the needs of industrial lands. As the flow of investments was increasing in Indonesia, then in 1989 private companies were allowed to developed industrial estates. In developing industrial estates especially at the pre-construction phase, there are some main phases have to be done such as permits stages, land acquisition, and planning stages. In planning stages, it will discuss the realisation of the given Technical Standard in land use planning, site planning, infrastructures and community facilities planning on several industrial estates in East Java. Abstract in Bahasa Indonesia : Kawasan Industri di Indonesia pertama kali dikembangkan oleh pemerintah melalui BUMN pada tahun 1970-an sebagai reaksi terhadap kebutuhan lahan industri. Dengan semakin meningkatnya arus investasi di Indonesia, baru kemudian pada tahun 1989 pihak swasta diperbolehkan mengembangkan kawasan industri. Dalam pengembangan kawasan industri khususnya pada tahapan pra-konstruksi, terdapat beberapa tahapan utama yang harus dilalui yaitu antara lain tahap perijinan, pembebasan tanah, dan tahap perencanaan. Pada tahap perencanaan akan dibahas tentang penerapan Standar Teknis yang ada dalam perencanaan penggunaan lahan, perencanaan tapak serta perencanaan prasarana dan sarana pada beberapa kawasan industri di Jawa Timur. Kata kunci: Pengembangan, Kawasan Industri.